Más luz sobre el rol de contenidos abiertos y moocs en la educación superior del s. XXI - Sancho, Teresa (Anuario ThinkEPI, 2015)
Reseñas de informes: Gaebel, Michael (2014). Moocs: Massive open onlice courses. An update of EUA´s first paper (January 2013). Brussels: European University Association,Â EUA occasional papers, January, 35 pp. http://www.eua.be/Libraries/Publication/MOOCs_Update_January_2014.sflb.ashx Â Kazakoff-Lane, Carmen (2014). Environmental scan and assessment of OERs, moocs and libraries: What effectiveness and sustainability means for libraries impact on open education. Chicago, IL:Â Association of College and Research Libraries. http://goo.gl/43JPLk